Enhancing Replacement Policy of Content-Centric Networking to Support Reaction toward Natural Disaster - Alubady, Raaid; AbdAlhadi, Samah; Abduladheem Kamil, Wesam (International Journal of Engineering and Technology, 2018)
Replacement policy in Content-Centric Networking (CCN) is a necessary and current, function as an important part in Interest packet caching. Pending Interest Table (PIT) is the main and core cache tables in CCN and plays a signiï¬cant role for recording the information of Interest packets that are forwarded but are still waiting for matching with incoming Data packets. However, PIT management is more fundamental with regard to CCN operations for better memory efï¬ciency. The PIT size determination of the forwarding system is a difficult problem in PIT management. Due to the limited PIT sizing, PIT replacement is utilized to remove the current entry from PIT and constructing a new space for the incoming entry to it. In a disaster area, this problem is due to the massive Interest packet that generating by survivors from the disaster and rescuers. The PIT overï¬‚ow could be subjected due to use of long Interest lifetimes that would simultaneously increase the number of entries in the PIT. Thus particularly when there is no flexible replacement policy, hence affecting PIT performance. Â Therefore, the ultimate aim of this paper is to develop the replacement policy that can deal with this problem. The proposed policy is a PIT management based on CCN PIT replacement policy forÂ  managing the PIT during a natural disaster, which can lead to mitigating PIT overï¬‚owing. The results showed the overall scenarios, the proposed policy better PIT memory usage as well as decreasing the Interest drop, delay time, Interest lifetime and Interest retransmission. A positive signiï¬cance inï¬‚uence in this work would be to presents a formulate a rule as a function which can decrease the delay and thus be leading to increasing PIT utilization, which will be very much useful for survivors, emergency rescue teams as well as emergency operation centers.Â Â